The Effect of Job Autonomy on Turnover Intention: Mediation Role of Work-Life Balance, and Job Satisfaction in the Banking Sector - Khusnul Rofida Novianti; Iqbal Ramadhani Fuadiputra (International Journal of Social Science and Business, 2021)
The banking sector is one of the sectors driving the Indonesian economy whose contribution is above. Banking activities are engaged in managing financial and non-financial products that are known to have a high employee turnover rate. The high level of employee turnover is influenced by various things, including work autonomy, work-life balance, and job satisfaction. For this reason, this study aims to examine the effect of work autonomy, work-life balance, and job satisfaction on turnover intention in the banking sector of Malang City. This study uses a quantitative approach with online questionnaire data collection. Data was collected by distributing questionnaires (online and offline) using a Likert scale ranging from 1-5. The population in this study were employees in the banking sector. The sample in this study uses a non-probability method with a sample size of 100. Data analysis uses Smart PLS (Partial Least Square) to describe the relationship between variables. The Sobel test was used to analyze the effect of the mediating variables, namely work-life balance and job satisfaction. The results showed that work autonomy significantly affected job satisfaction, work-life balance, and turnover intention. Work-life balance also has a significant effect on turnover intention. However, job satisfaction has no significant effect on turnover intention. In terms of mediating effects, work-life balance can mediate the effect of job autonomy on turnover intention. Meanwhile, job satisfaction has no mediating effect between work autonomy and turnover intention.